Game Portability Using a Service-Oriented Approach. (7th January 2008) - BinSubaih, Ahmed; Maddock, Steve
Abstract : Game assets are portable between games. The games themselves are, however, dependent on the game engine they were developed on. Middleware has attempted to address this by, for instance, separating out the AI from the core game engine. Our work takes this further by separating the game from the game engine, and making it portable between game engines. The game elements that we make portable are the game logic, the object model, and the game state, which represent the game's brain, and which we collectively refer to as the game factor, or G-factor. We achieve this using an architecture based around a service-oriented approach. We present an overview of this architecture and its use in developing games. The evaluation demonstrates that the architecture does not affect performance unduly, adds little development overhead, is scaleable, and supports modifiability.